Rancang Bangun Aplikasi Penjualan Pakaian Untuk Meningkatkan Customer Experience - Herwanda Ayu Destania; Tri Sagirani; Julianto Lemantara (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Ababil has various problems, namely wrong orders because there is no system that records, types of product information, catalogs, menu consultations, and no promos. Problems are analyzed with customer journal mapping and produce features that customers need. Testing with the blackbox method on functionality is declared effective. Based on the SUS trial, the sales application interface design falls into the grade B scale category and the average result is 80.1. This means that the interface design is acceptable. The results of the in-depth interview menu made on the Ababil clothing sales website according to the CX indicator, including: the main page increases the taste indicator because it relates to the senses in placing an order, product details are in accordance with actions related to the customer's physical, order history is an indicator that refers to customer's feeling of wearing. The discussion menu, FaQ, chat increase the relate indicator because it is connected between other people and the company or other. Menu vouchers improve thinking indicators by surprise, menu reviews include act indicators because they prevent ignoring criticism and suggestions. The comparison between pre-survey that 72.2% of 36 respondents were dissatisfied, with post-survey the level of dissatisfaction decreased by 63.9%.